Cytokine profile in patients with chronic myeloid leukemia - T. N. Aleksandrova; I. I. Mulina; A. S. Lyamkina; A. A. Studenikina; N. A. Varaksin; E. S. Mikhaylova; T. I. Pospelova; A. I. Autenshlyus (Медицинская иммунология, 2024)
Resistance to tyrosine kinase inhibitors (TKIs) is currently an important clinical problem in the management of patients with chronic myeloid leukemia (CML). Recent studies suggested that aberrant cytokine secretion may be among the BCR/ABL-independent mechanisms of resistance, thus contributing to the persistence of leukemic stem cells in spite of continuous targeted therapy. The aim of the study was to evaluate concentration of cytokines in the serum of patients with CML depending on the efficiency of therapy.Quantitative determination of the cytokines (TNFα, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-17, IL-18, IFNα and VEGF) in blood serum of patients with chronic-phase CML (n = 84) and healthy subjects (n = 30) was performed using enzyme immunoassay (ELISA). The patients with CML were divided into 3 groups depending on the duration of therapy: group I, newly diagnosed patients (n = 10); group II, patients receiving therapy for < 12 months (n = 10); group III included patients receiving therapy for more than 12 months (n = 64).The results of our study showed that cytokine concentration among CML patients significantly differed, depending on the duration of therapy. Significantly higher concentration of IL-17, IL-6, IL-1β, IL-10, IL-18, IL-2 and TNFα was found in group I compared with control group. Group II patients also demonstrated significantly higher concentrations of TNFα, IL-6, IL-10, IL-18 and IFNα by comparison with control group, as well as higher concentration of IFNα compared with in groups I and III. In group III, concentrations of IL-17, IL-1β, TNFα, IL-6, IL-10, IL-18 were significantly higher than in control group. When compared with group I, it was found that concentrations of IL-1β, IL-2 and IL-18 were significantly lower. A direct correlation was found between expression levels of chimeric BCR/ABL gene, (a marker of CML malignancy), and concentrations of IL-1β and IL-17. ROC-analysis demonstrated high-quality models which showed an association between achievement of major molecular response (MMR) and low serum concentrations of IL-1β, IL-6 and IL-17.Hence, the results of our study have shown that determination of IL-1β, IL-6 and IL-17 concentrations may be a prognostic marker for assessing the efficiency of therapy and probability of achieving MMR in CML.